Case report: Urbanized non-human primates as sentinels for human zoonotic diseases: a case of acute fatal toxoplasmosis in a free-ranging marmoset in coinfection with yellow fever virus - Davi E. R. Sousa; Davi E. R. Sousa; Tais M. Wilson; Tais M. Wilson; Isabel L. Macêdo; Isabel L. Macêdo; Alessandro P. M. Romano; Daniel G. Ramos; Pedro H. O. Passos; Gabriela R. T. Costa; Gabriela R. T. Costa; Vagner S. Fonseca; et al. (Frontiers Media S.A., 2023)
Free-ranging non-human primates (NHP) can live in anthropized areas or urban environments in close contact with human populations. This condition can enable the emergence and transmission of high-impact zoonotic pathogens. For the first time, we detected a coinfection of the yellow fever (YF) virus with Toxoplasma gondii in a free-ranging NHP in a highly urbanized area of a metropolis in Brazil. Specifically, we observed this coinfection in a black-tufted marmoset found dead and taken for a necropsy by the local health surveillance service. After conducting an epidemiological investigation, characterizing the pathological features, and performing molecular assays, we confirmed that the marmoset developed an acute fatal infection caused by T. gondii in coinfection with a new YF virus South American-1 sub-lineage. As a result, we have raised concerns about the public health implications of these findings and discussed the importance of diagnosis and surveillance of zoonotic agents in urbanized NHPs. As competent hosts of zoonotic diseases such as YF and environmental sentinels for toxoplasmosis, NHPs play a crucial role in the One Health framework to predict and prevent the emergence of dangerous human pathogens.